Trend and Temporal Variability of Drought in Kirklareli Province Using Reconnaissance Drought Index and Standardized Precipitation Index - Mustafa Utku Yılmaz (Doğal Afetler ve Çevre Dergisi)
This study aimed to provide a comprehensive drought analysis for Kırklareli province, whose economy is largely based on agriculture. The trend and temporal variability of drought were examined at 1, 3, 6, 9, and 12-month time scales using the Standardized Precipitation Index (SPI) and Reconnaissance Drought Index (RDI). The monthly precipitation and temperature data from the Kırklareli meteorological station between water years 1960-2021 were used to calculate the SPI and RDI. Mann-Kendall and modified Mann-Kendall tests were used to determine trends of SPI and RDI series for different time scales, Sen’s slope was used to identify the magnitude of trends in the series, and Pettitt's test was used to detect the change point of the series. The results revealed that the SPI and RDI behaved similarly for all time scales and both indices were able to capture almost the same drought events. Besides, it was observed that SPI had a strong linear relationship with RDI over the same time scale (r=0.99). RDI mostly had slightly higher values than SPI and it was concluded that RDI was more sensitive in the detection of extreme and severe drought events. The percentages of occurrence of drought events at different time scales ranged from 46.9% to 51.3% for SPIs and between 47.2% and 50.6% for RDIs. In the 12-month time scale for both indices, 76 months between February 1989 and May 1995 were determined as both the longest and the most severe dry period. As the time scale increased, the number of drought events decreased and the drought duration increased. No statistically significant trend was found for SPI and RDI values at all-time scales (p>0.05). For both indices, there was no change point in the 1-month time scale, but the change point was identified in the 3, 6, 9, and 12-month time scales.